2017
DOI: 10.1063/1.5003542
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study on early strength of sodium hydroxide (NaOH) activated fly ash based geopolymer

Abstract: Abstract. The urge to reduce carbon dioxide (CO2) emission has encourage researchers to introduce environmental friendly binder or known as geopolymer. This new binder was produced by mixing source materials rich in silica and alumina with alkaline liquids. For this study, class F fly ash was used as source material with two different types of alkaline activator; sodium hydroxide (NaOH) only and a combination of water glass with NaOH. The different concentration of the NaOH solutions (8M, 10M, 12M and 14M) is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 12 publications
1
4
1
2
Order By: Relevance
“…Accordingly, it can be deduced from these findings that at the initial stages the reaction process is faster. These findings are quite the opposite of [44]. Fig.…”
Section: Resultsmentioning
confidence: 77%
“…Accordingly, it can be deduced from these findings that at the initial stages the reaction process is faster. These findings are quite the opposite of [44]. Fig.…”
Section: Resultsmentioning
confidence: 77%
“…The mortars MCA0.35 and MCT0.33 exhibit slightly higher absorption values (1.36 and 1.37%), due to the greater water content. Nevertheless, all the one-part AAMs prepared show suitable water absorption values (<5%), above which their compressive strength can be compromised [ 39 ]. In addition, the typical water absorption values for mortars with OPC vary between 15 and 18% [ 40 ], while for traditional AAMs they are slightly lower, from 5 to 11% [ 41 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…The authors observed that the workability and setting time of the AMMs mixtures prepared with sodium silicate did not fill the requirements, even when additives were used, and a decrease of the compressive strength was observed. On the contrary, in the mixtures prepared with anhydrous sodium metasilicate, it was possible to adjust the pastes' workability and the setting time leading to interesting mechanical properties (37)(38)(39)(40)(41)(42)(43)(44)(45).…”
Section: Introductionmentioning
confidence: 99%
“…O processo de geopolimerização necessita de um menor consumo energético pode ser realizado pelo uso de subprodutos industriais (NATH et al, 2016). Em relação ao consumo de energia e a emissão de gases de estufa, o cimento geopolimérico emite 80% menos de CO2 e consome 30-40% menos de energia do que o cimento Portland, em sua produção (YAHYA et al, 2017).…”
Section: Introductionunclassified
“…O desenvolvimento da microestrutura geopolimérica é dependente das características das matérias-primas e de parâmetros do processo, especialmente da concentração alcalina da solução ativadora utilizada e da temperatura de cura (YAHYA et al, 2017). Estudos têm demonstrado que a temperatura de cura é um parâmetro que tem papel importante no processo geopolimerização (NATH et al, 2016).…”
Section: Introductionunclassified